EVALUATION OF THE EFFECTIVENESS OF LOCAL CLAY FOR USE AS WATER-BASED DRILLING MUD (A CASE STUDY OF AMAI IN UKWUANI L.G.A, DELTA STATE) - Igili, Chinedu; Okonkwo, John; Ogbimi, Emofe; Chinyem, Felix; Enebrayekedou, Ezekiel (FUDMA Journal of Sciences, 2026)
This study evaluates the effectiveness of clay deposits from Amai-Nge and Umubu communities in Ukwuani Local Government Area, Delta State, Nigeria, for application in water-based drilling mud systems as potential alternatives to imported bentonite. Clay samples were processed and formulated into drilling fluids, while rheological and filtration properties were determined according to API recommended practice (API RP-13B). Initial characterization of raw clays showed inferior performance relative to commercial bentonite, with Amai and Umubu samples exhibiting low plastic viscosity (1–2 cP), low apparent viscosity (4.5–5.0 cP), and acidic pH values of 5.77–6.14 compared with bentonite values of 8 cP, 13 cP, and pH 10.0, respectively. Following beneficiation using sodium carbonate (Na₂CO₃) and barite (BaSO₄), significant improvements were observed. Beneficiated Umubu clay demonstrated plastic viscosity of 5 cP (150% increase), apparent viscosity of 15 cP (200% increase), and yield point of 20 lb/100 ft² (233% increase), surpassing commercial bentonite by approximately 15.4% in apparent viscosity and 81.8% in yield point. pH increased from 6.14 to 10.05, achieving API-compliant alkaline conditions, while filter cake thickness (1.05 mm) remained within acceptable API limits. The Amai clay showed moderate enhancement but remained below commercial performance levels. The results demonstrate that with proper beneficiation, Umubu clay can serve as a cost-effective substitute for imported bentonite in water-based drilling fluid systems.